Novel Carbon Dots Derived from Puerariae lobatae Radix and Their Anti-Gout Effects - Wang, Xiaoke; Zhang, Yue; Zhang, Meiling; Kong, Hui; Wang, Suna; Cheng, Jinjun; Qu, Huihua; Zhao, Yan (Molecules (Basel, Switzerland), 2019)
Gout is a disease with a high incidence and causing great harm, and the current treatment drugs are not satisfactory. In this study, novel water-soluble carbon dots (CDs) with anti-gout effect, named Puerariae lobatae Radix CDs (PLR-CDs), are reported. PLR-CDs were synthesized with an improved pyrolysis method at 300 °C, and their characterization was performed with multifaceted approaches, such as transmission electron microscopy (TEM) and ultraviolet–visible (UV–vis) and Fourier-transform infrared (FTIR) spectroscopy. In addition, the biocompatibility of PLR-CDs was studied using the cell counting kit (CCK)-8 in LO2 cells and RAW264.7 cells, and the anti-gout activity of PLR-CDs was examined on animal models of hyperuricemia and gouty arthritis. The characterization of PLR-CDs indicated that they were nearly spherical, with diameters ranging from 3.0 to 10.0 nm, and the lattice spacing was 0.283 nm. The toxicity experiment revealed that PLR-CDs were non-poisonous for LO2 cells and RAW264.7 cells at concentrations below 250 μg/mL. The results of pharmacodynamic experiments showed that PLR-CDs could lower the blood uric acid level in model rats by inhibiting the activity of xanthine oxidase and reduce the degree of swelling and pathological damage of gouty arthritis. Thus, PLR-CDs with anti-gout biological activity and good biocompatibility have the prospect of clinical application for the treatment of gout.